2017
DOI: 10.3389/fnins.2016.00620
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Fat Appetite after Roux-en-Y Gastric Bypass Surgery Associates with Reduced Brain μ-opioid Receptor Availability in Diet-Induced Obese Male Rats

Abstract: Brain μ-opioid receptors (MORs) stimulate high-fat (HF) feeding and have been implicated in the distinct long term outcomes on body weight of bariatric surgery and dieting. Whether alterations in fat appetite specifically following these disparate weight loss interventions relate to changes in brain MOR signaling is unknown. To address this issue, diet-induced obese male rats underwent either Roux-en-Y gastric bypass (RYGB) or sham surgeries. Postoperatively, animals were placed on a two-choice diet consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…For instance, duodenal-jejunal exclusion, a procedure that leaves the stomach intact, is significantly less effective at reducing feeding or body weight in animals and humans ( Geloneze et al, 2009 ; Kindel et al, 2011 ; Alvarez et al, 2020 ). In further support of our model, adding gastric vagotomy to gastrectomy does not produce further weight-loss in laboratory rodents ( Hankir et al, 2016 ; Dezfuli et al, 2018 ). This is logical considering that gastric vagotomy already occurred in bypassed subjects.…”
Section: Predictions and Consistency With The Literaturesupporting
confidence: 68%
“…For instance, duodenal-jejunal exclusion, a procedure that leaves the stomach intact, is significantly less effective at reducing feeding or body weight in animals and humans ( Geloneze et al, 2009 ; Kindel et al, 2011 ; Alvarez et al, 2020 ). In further support of our model, adding gastric vagotomy to gastrectomy does not produce further weight-loss in laboratory rodents ( Hankir et al, 2016 ; Dezfuli et al, 2018 ). This is logical considering that gastric vagotomy already occurred in bypassed subjects.…”
Section: Predictions and Consistency With The Literaturesupporting
confidence: 68%
“…Rats receiving RYGB display higher morphine self-administration rates than lean, obese, and caloric intake-matched counterparts [16]. The downregulated MOR signaling reported here and by others supports this notion [33]. No studies have of yet investigated the effect of administered MOR agonists or antagonists on feeding or motivated behavior following RYGB, which could provide further insight into the induced changes in reward signaling.…”
Section: Discussionsupporting
confidence: 69%
“…RYGB has been shown to reduce preferences for highly palatable sugars and fat in rats, an effect that had been initially attributed to altered reward functions [29, 30], while more recent works in rats and human debate that notion [31, 32]. Moreover, RYGB surgery in HF diet-fed rats has been demonstrated to reduce brain MOR availability in the hypothalamus, amygdala, and striatum as measured by [ 11 C]carfentanil PET imaging, and reduce MOR protein expression in the striatum and prefrontal cortex, compared to those receiving sham surgery [33] These changes in opioid signaling were accompanied by decreased HF diet intake and preference in the RYGB group.…”
Section: Introductionmentioning
confidence: 99%
“…Subcutaneous administration of the non-selective opioid receptor antagonist, naltrexone, reduced the acquisition of fat reinforcement, but not the expression of learned reinforcement [ 167 ]. In rats, a roux-en-Y gastric bypass markedly suppressed fat intake and preference, and downregulated MOR protein levels in the striatal and prefrontal areas [ 168 ]. Overall, the current literature has suggested that the opioid system plays a major role in fat preference.…”
Section: Macronutrient-based Diet Selection (What We Eat)mentioning
confidence: 99%